Between the Imagined and the Reality: Threat of African Invasion and Spain's Migration Policy in sub-Saharan Africa - Agyeman, Edmond Akwasi (African Human Mobility Review, 2021)
The paper examines Spain's migration policy aimed at controlling sub-Saharan African immigration. It is based on analysis of policy documents, migration statistics and secondary literature. The paper shows that current migratory trends and statistics do not support the perception that sub-Saharan African migrants are invading Spain. The paper shows that Spain's policy of walling itself off the African continent is borne out of an imaginary threat and Spain's role as a gatekeeper for Western Europe's southern borders. It further argues that Spain's restrictive policies ignore the long-standing interdependent trade and other economic networks that exist between Spain, North Africa and West Africa, which predate the European colonization of Africa.